Identification of multi-drug resistant Pseudomonas aeruginosa clinical isolates that are highly disruptive to the intestinal epithelial barrier - Shevchenko Olga; Bethel Cindy; Wang Yingmin; Kohler Jonathan E; Zaborina Olga; Wu Licheng; Turner Jerrold R; Alverdy John C (BMC, 2006)
Abstract Background Multi-drug resistant Pseudomonas aeruginosa nosocomial infections are increasingly recognized worldwide. In this study, we focused on the virulence of multi-drug resistant clinical strains P. aeruginosa against the intestinal epithelial barrier, since P. aeruginosa can cause lethal sepsis from within the intestinal tract of critically ill and immuno-compromised patients via mechanisms involving disruption of epithelial barrier function. Methods We screened consecutively isolated multi-drug resistant P. aeruginosa clinical strains for their ability to disrupt the integrity of human cultured intestinal epithelial cells (Caco-2) and correlated these finding to related virulence phenotypes such as adhesiveness, motility, biofilm formation, and cytotoxicity. Results Results demonstrated that the majority of the multi-drug resistant P. aeruginosa clinical strains were attenuated in their ability to disrupt the barrier function of cultured intestinal epithelial cells. Three distinct genotypes were found that displayed an extreme epithelial barrier-disrupting phenotype. These strains were characterized and found to harbor the exoU gene and to display high swimming motility and adhesiveness. Conclusion These data suggest that detailed phenotypic analysis of the behavior of multi-drug resistant P. aeruginosa against the intestinal epithelium has the potential to identify strains most likely to place patients at risk for lethal gut-derived sepsis. Surveillance of colonizing strains of P. aeruginosa in critically ill patients beyond antibiotic sensitivity is warranted.